FUNCTIONALITY EVALUATION OF EXCIPIENTS MANUFACTURED BY DIFFERENT MANUFACTURERS - BS Muddukrishna (Journal of Global Pharma Technology, 2016)
Purpose: The main aim of this article is to develop an alternate source for excipients manufactured bydifferent manufacturers. Methods: Four different excipients were selected for this study and evaluated based on theirfunctional characteristics. Results: From the results obtained, the both vendors of the materials were showingequivalent each other when we compared with the monograph specifications, analytical results and functionalitycharacteristics. Conclusion: Functionality evaluation of excipients were determined based on the specificationcomparison, analytical results comparison and finally with functionality characteristics of excipients and their impacton formulation.